Experimental Investigations on Pullout Behavior of HDPE Geogrid under Static and Dynamic Loading - Zheng Zuo; Guangqing Yang; He Wang; Zhijie Wang (Advances in Materials Science and Engineering)
This paper describes a series of laboratory pullout tests that were performed to investigate the pullout behavior of high-density polyethylene (HDPE) uniaxial geogrid subjected to static and dynamic loading. Pullout tests were conducted on HDPE geogrid reinforced coarse sand under normal static loading (60–300 kPa), dynamic loading with different amplitudes (20, 40, and 60 kPa), and different frequencies (2, 4, and 6 Hz) by using the newly developed pullout apparatus. The results indicated that the pullout resistance of geogrid presented different growth patterns with the increase of normal loads under static loading. The amplitude and frequency both had significant effects on the interaction between reinforcement and soil, and the increment of the pullout resistance was 0.6 kN and 0.3 kN, respectively. The effect of dynamic loading on the soil-geogrid interface can be gradually equivalent to that of static loading corresponding to the balance position of dynamic loading with the increase of frequency compared with the static loading. The results of this study are helpful for the selection of the strength of the reinforcement in different locations and to simplify the study on the stress of reinforcement in reinforced soil structures under traffic loads.